THE ROLE OF TECHNOLOGY IN PEDAGOGICAL DESIGN IN IMPROVING THE QUALITY OF EDUCATION - Kadirjanovna, Abdurakhmanova Dilrabo; Muhammadzhonovna, Karimova Nargiza; Sharopovna, Bozorova Rufina; Anvarjon qizi, Saydaliyeva Mashxura; Maxammadjonovna, Sadriddinova Dildora (International Journal of Psychosocial Rehabilitation, 2020)
The term "pedagogical technology" today is one of the most relevant in pedagogical circles. Everywhere in higher pedagogical educational institutions corresponding courses or special courses are introduced, and a lively discussion is conducted in the literature, indicating that this concept has not only theoretical, but also practical significance.The most famous researchers of pedagogical technology include Yu.K. Babansky, V.P. Bespalko, I.P. Volkova, G.I.Zhelezovskaya, V.I. .V. Klarina, B.T. Likhacheva, V.M. Leonov, L.N. Landa, P.I. Pidkasisty, P.Ya. Talyzin, P.M. Erdiev, B. Blum, D. Bruner, G. .Gays, V. Coskarelli, J. Carroll, V. Okon, • Sakomoto, B.F. Skinner, D, Khamblin, F. Yanushkevich.